Deteksi Foto Manipulasi Dengan Tools Forensicallybeta dan Imageforensic.org Dengan Metode Error Level Analysis (ELA) - Harahap, Fitriana (TIN: Terapan Informatika Nusantara, 2021)
The development of the current digital era, makes a photo easily manipulated so that it can change the information conveyed to be different and make it vulnerable to being used for crime. Digital image forensics is one of the scientific ways to prove the authenticity of photos. The purpose of this research is to analyze a digital image that has been manipulated or engineered using certain software or programs. While the analysis tool uses the Error Level Analysis (ELA) method introduced by Krawetz. The tools used are web-based Imageforensics (http://imageforensic.org//) and ForensicallyBeta (https://29a.ch/photo-forensics/#forensicmagnifier). The results obtained from this study are the detection of differences in noise contrast between the original photo and the manipulated photo, which indicates a change in the photo. Photo manipulation by means of image splicing generally produces darker spots, while the original photo produces lighter spots